Twelve-month prevalence of haemarthrosis and joint disease using the Haemophilia Joint Health score: evaluation of the UK National Haemophilia Database and Haemtrack patient reported data: an observational study. Issue 1 (12th January 2022) - Wilkins, Richard A; Stephensen, David; Siddle, Heidi; Scott, Martin J; Xiang, Hua; Horn, Elizabeth; Palmer, Ben; Chapman, Graham J; Richards, Michael; Walwyn, Rebecca; Redmond, Anthony
Abstract : Objectives: To report the 12-month prevalence of joint bleeds from the National Haemophilia Database (NHD) and Haemtrack, a patient-reported online treatment diary and concurrent joint disease status using the haemophilia joint health score (HJHS) at individual joint level, in children and adults with severe haemophilia A and B (HA/HB) without a current inhibitor. Design: A 2018 retrospective database study of NHD from which 2238 cases were identified, 463 patients had fully itemised HJHS of whom 273 were compliant in recording treatment using Haemtrack. Setting: England, Wales and Scotland, UK. Participants: Children (<18 years) and adults (≥18 years) with severe HA and HB (factor VIII/factor IX, <0.01 iu/mL) without a current inhibitor. Primary and secondary outcomes: Prevalence of joint haemarthrosis and concurrent joint health measured using the HJHS. Results: The median (IQR) age of children was 10 (6–13) and adults 40 (29–50) years. Haemarthrosis prevalence in HA/HB children was 33% and 47%, respectively, and 60% and 42%, respectively, in adults. The most common site of haemarthrosis in children was the knee in HA and ankle in HB. In adults, the incidence of haemarthrosis at the ankles and elbows was equal. The median total HJHS in HA/HB children was 0 and in adults with HA/HB, were 18 and 11, respectively. In adults with HA/HB, the median ankle HJHS of 4.0 was higher than the median HJHS of 1.0 for both the knee and elbow. Conclusion: Despite therapeutic advances, only two-thirds of children and one-third of adults were bleed-free, even in a UK cohort selected for high compliance with prophylaxis. The median HJHS of zero in children suggests joint health is relatively unaffected during childhood. In adults, bleed rates were highest in ankles and elbows, but the ankles led to substantially worse joint health scores.